Amorphous Cr/SiO2 Materials Hydrothermally Treated: Liquid Phase Cyclohexanol Oxidation - Miranda, José Feliciano (2018)
Amorphous Cr–SiO2 materials were synthesized by the sol–gel method and hydrothermally treated at temperatures between 150 and 220 °C. These materials were used as catalysts for cyclohexanol oxidation with H2O2 as oxidant and CH3CN as a solvent. They were responsible for the decomposition of H2O2, which triggers, by a free radical mechanism in the homogeneous phase, the oxidation or degradation of the hydrocarbon chain. Metal leaching causes a drop in catalytic activity when the material is recycled. Studies on the hydrothermal treatment effect on the leaching process have demonstrated that the higher the hydrothermal treatment temperature, the higher the metal/support interaction, leading to a diminution of the leaching process. Under mild reaction conditions, and using TBHP as oxidant, leaching was reduced, and improvements were obtained on the selectivity towards the formation of cyclohexanone. The use of these catalysts in the oxidation of verbenol, an allylic alcohol, showed a significant increase in the substrate conversion and in the selectivity to carbonyl derivative formation.